Application of geochemical modelling for hydraulic stimulation in enhanced geothermal systems. Issue 6 (1st November 2020) - Lee, Junbeum; Chung, Eunhyea
ABSTRACT: In an enhanced geothermal system (EGS), the use of fracking fluid generally causes changes in the geochemical properties of a hydrothermal reservoir. In this study, the geochemical changes were estimated through geochemical modelling using PHREEQC, and the modelling results were compared with field data and evaluated. As a result, the model showed an increase of the electrical conductivity in time which is consistent with the measurements. From the comparison between two results, it was found that the injected water was mixed with groundwater and the influence of the groundwater was significant when the hydraulic retention time of the fluid was longer than a day. Also, the chemical properties of the bedrock groundwater significantly could influence on the geochemical reactions in the geothermal reservoir. From the results, it can be concluded that the consideration of the chemical properties of groundwater or formation water is essential for the successful EGS operation.